Application advance of electrosprayed micro/nanoparticles based on natural or synthetic polymers for drug delivery system. (August 2022) - Zhao, Shiyi; Huang, Chi; Yue, Xuan; Li, Xuebo; Zhou, Ping; Wu, Anxin; Chen, Chonghao; Qu, Yan; Zhang, Chen
Graphical abstract: Highlights: Electrospray as a novel method to prepare micro/nanoparticles are described. Illustrated a variety of polymer used in electrosprayed microspheres. Presented the application of electrosprayed micro/nanoparticles in drug delivery. Future perspectives of electrospray in combination with medical field are discussed. Abstract: Micro/nanoparticles-based drug delivery system has emerged significantly and has influenced the pharma industry up to considerable extent. At the same time, the development of production methods that are cost effective, scalable and reproducible becomes crucial to ensure the clinical translation of any development. The application of electrospray (ES) technology in micro-nano drug delivery system not only has the above advantages, but also can quickly obtain uniform and stable micro/nanoparticles as drug carriers through its own characteristics. Natural or synthetic polymers are often used as raw materials for these micro/nanoparticles. The micro/nanoparticles carriers prepared by these polymers can change the solubility and bioavailability of drugs and reduce the toxicity caused by mass accumulation after sudden drug release. And after reaching the target site, they're easy to degrade and will not accumulate in the body. In this review, taken together, we briefly describe the principle and advantages of ES, as well as the common polymers for the preparation of micro/nanoparticles by this method. The types of electrosprayed micro/nanoparticles and their advantages as micro-nano drug delivery systems in different drug delivery routes and different diseases were also discussed. And prospects are made for the future development of electrospray in the field of medicine.